EVALUASI KEBIJAKAN PENJADWALAN PEMADAMAN LISTRIK BERGILIR PADA JAM ISTIRAHAT MELALUI PERSPEKTIF KOMUNIKASI KRISIS: STUDI PADA PENGGUNA RUMAH TANGGA - Rosya Amalia; Dewi Rahmawati; Tria Patrianti (PT. Hasba Edukasi Mandiri, 2026)
Rolling blackouts implemented by Indonesia's state electricity utility (PLN) throughout mid-2026, particularly those scheduled during evening and night hours that overlap with household rest time, have raised public concern not only about service reliability but also about the quality of crisis communication accompanying the policy. This study evaluates PLN's crisis communication practices during rolling blackout events in several regions of Indonesia (Java, West Kalimantan, and South-Central Kalimantan) between June and July 2026, using Coombs' Situational Crisis Communication Theory (SCCT) and Benoit's Image Repair Theory as analytical lenses. Using a qualitative case-study approach with media content analysis of news reports, official statements, and publicly recorded household responses, the study finds that PLN predominantly relied on justification and rebuild strategies, technical explanations of generator disturbances combined with public apologies, while proactive notification channels such as WhatsApp and social media were frequently issued at times poorly aligned with household rest hours, which reduced the perceived transparency and timeliness of the communication. The study argues that crisis communication protocols for essential-service disruptions must explicitly account for the timing of message delivery relative to the audience's daily rhythm, not only the content and tone of the message. Practical recommendations for utility communication management are offered.